The Potential Role of Ecotourism in Sustainable Development: A Systematic Review - XABA, Fikile; ADANLAWO, Eyitayo Francis (Journal of Ecohumanism, 2024)
This study aims to establish the relationship between sustainable development and ecotourism and showcase how ecotourism can contribute to sustainable development. Result from systematic review revealed that community access to ecotourism opportunities is limited, thereby limiting its contribution to sustainable development. The study concludes that for ecotourism to contribute to sustainable development in local communities, there is a need to reduce social inequality and motivate local community members to contribute to the protection of the local environment and culture. The implications are that ecotourism initiatives can benefit local communities if they are involved in the planning, execution, and control of ecotourism projects.